DOLAP data warehouse research over two decades: Trends and challenges. (November 2019) - Wrembel, Robert; Abelló, Alberto; Song, Il-Yeol
Abstract: This paper introduces to the Information Systems special issue, including the four best papers submitted to DOLAP 2018. Additionally, the 20th anniversary of DOLAP motivated the analysis of DOLAP topics, as follows. First, the recent 5-years DOLAP topics were confronted with those of VLDB, SIGMOD, and ICDE. Next, the DOLAP topics were analyzed within its 20 years of history. Finally, the analysis is concluded with the list of the most frequent research topics of the aforementioned conferences and still open research problems.